Treasure island - Wilkes, Angela; Taplin, Sam Dennis, Peter Stevenson, Robert Louis (Usborne London, 2007)
The classic adventure story by Robert Louis Stevenson re-told for children growing in reading confidence and ability. When Jim Hawkins sets sail searching for buried treasure and adventure, he finds himself caught up in a deadly mutiny where he must outwit the cunning pirate Long John Silver in order to stay alive.